Functional analysis of OCTN2 and ATB(0,+) in normal human airway epithelial cells - Rotoli, Bianca Maria (PLoS One, 2020)
In human, OCTN2 (SLC22A5) and ATB(0,+) (SLC6A14) transporters mediate the uptake of L-carnitine, essential for the transport of fatty acids into mitochondria and the subsequent degradation by β-oxidation. Aim of the present study was to characterize L-carnitine transport in EpiAirway(™), a 3D organotypic in vitro model of primary human tracheal-bronchial epithelial cells that form a fully differentiated, pseudostratified columnar epithelium at air-liquid interface (ALI) condition. In parallel, Calu-3 monolayers grown at ALI for different times (8d or 21d of culture) were used as comparison. OCTN2 transporter was equally expressed in both models and functional at the basolateral side. ATB(0,+) was, instead, highly expressed and active on the apical membrane of EpiAirway(™) and only in early-cultures of Calu-3 (8d but not 21d ALI). In both cell models, L-carnitine uptake on the apical side was significantly inhibited by the bronchodilators glycopyrrolate and tiotropium, that hence can be considered substrates of ATB(0,+); ipratropium was instead effective on the basolateral side, indicating its interaction with OCTN2. Inflammatory stimuli, such as LPS or TNFα, caused an induction of SLC6A14/ATB(0,+) expression in Calu-3 cells, along with a 2-fold increase of L-carnitine uptake only at the apical side; on the contrary SLC22A5/OCTN2 was not affected. As both OCTN2 and ATB(0,+), beyond transporting L-carnitine, have a significant potential as delivery systems for drugs, the identification of these transporters in EpiAirway(™) can open new fields of investigation in the study of drug inhalation and pulmonary delivery.